Responses of Microbial Nutrient Acquisition to Depth of Tillage and Incorporation of Straw in a Chinese Mollisol - Zhang, Naiwen; Chen, Xu; Han, Xiaozeng; Lu, Xinchun; Yan, Jun; Zou, Wenxiu; Yan, Lei (Frontiers in Environmental Science, 2021)
Tillage and straw incorporation are important agricultural practices that can break the plow layer and improve Mollisol fertility. The effect of these practices on the limitation of resources for soil microorganisms, however, is unclear. We established a field experiment in 2018 and collection of soil samples in 2020 to study the acquisition of resources by microbes in a Mollisol region in northeastern China. Four treatments were studied: conventional tillage (CT), straw incorporation with conventional tillage (SCT), subsoil tillage (ST) and straw incorporation with subsoil tillage (SST). The limitation of resources for soil microorganisms was assessed using models of extracellular enzymatic stoichiometry. The soil microbes were generally colimited by C and P but not N. The degree of limitation, however, varied among the treatments. SCT and SST alleviated microbial P limitation in the 0-15 and 15-35 cm layers, respectively, but ST did not significantly affect P limitation relative to CT. Interestingly, N-resource contents were strongly correlated with indicators of C and P limitation. A random forest analysis found that the contents of available N and total dissolved N were the most important factors for microbial C and P limitation, respectively. Straw incorporation alleviated microbial P limitation but did not eliminate P limitation and deep tillage aggravate microbial C limitation. We suggest that N fertilization may be reduced due to the N-rich characteristics of the Mollisols in northeastern China.